Epidemiology, outcome, targeted agents and immunotherapy in adolescent and young adult non‐Hodgkin and Hodgkin lymphoma. (6th February 2019) - Metzger, Monika L.; Mauz‐Körholz, Christine
Summary: The epidemiology, outcome and targeted immunotherapy in adolescent and young adult non‐Hodgkin and Hodgkin lymphoma were discussed during the 6th International Symposium on Childhood, Adolescent and Young Adult Non‐Hodgkin Lymphoma September 26th–29th 2018 in Rotterdam, the Netherlands. This review summarizes some of those presentations, as well as other current and novel antibody therapy, immune check‐point inhibitors, chimeric antigen receptor T cells, cancer vaccines and cytotoxic T lymphocyte therapy.